Food Supply and Food Security of the World’s Population in the Conditions of Changing World Order: Management Aspects - A. M. Holdoenko (Управленческое консультирование)
Geopolitical changes lead to a transformation of the economy and social conditions for the livelihoods of the population. Different population densities, land fertility, and differences in income levels initiate the use of different approaches to providing the world’s population with food. The impact of sanctions against Russia on food supply and food security in the world, in particular considering the “grain deal,” remains poorly understood. The purpose of the work is to analyze the processes of food supply and achieving food security in the countries of the world, considering the introduction of sanctions by Western countries against Russia. The objectives of the study are as follows: to analyze the current situation in food supply, to identify the main threats to food security in the world as a whole, to propose solutions to reduce the negative impact of sanctions imposed against some states on third countries. The results of the study provide substantiation of proposals aimed at resolving issues of ensuring food security in the world under sanctions pressure on exporters of agricultural products.